GASP XXV: neutral hydrogen gas in the striking jellyfish galaxy JO204. Issue 4 (23rd April 2020) - Deb, Tirna; Verheijen, Marc A W; Gullieuszik, Marco; Poggianti, Bianca M; van Gorkom, Jacqueline H; Ramatsoku, Mpati; Serra, Paolo; Moretti, Alessia; Vulcani, Benedetta; Bettoni, Daniela; Jaffé, L Yara; Tonnesen, Stephanie; et al.
ABSTRACT: We present JVLA-C observations of the H i gas in JO204, one of the most striking jellyfish galaxies from the GASP survey. JO204 is a massive galaxy in the low-mass cluster A957 at z = 0.04243. The H i map reveals an extended 90 kpc long ram-pressure stripped tail of neutral gas, stretching beyond the 30 kpc long ionized gas tail and pointing away from the cluster centre. The H i mass seen in emission is $(1.32± 0.13) × 10^{9} \, \rm M_{\odot }$, mostly located in the tail. The northern part of the galaxy disc has retained some H i gas, while the southern part has already been completely stripped and displaced into an extended unilateral tail. Comparing the distribution and kinematics of the neutral and ionized gas in the tail indicates a highly turbulent medium. Moreover, we observe associated H i absorption against the 11 mJy central radio continuum source with an estimated H i absorption column density of 3.2 × 10 20 cm −2 . The absorption profile is significantly asymmetric with a wing towards higher velocities. We modelled the H i absorption by assuming that the H i and ionized gas discs have the same kinematics in front of the central continuum source, and deduced a wider absorption profile than observed. The observed asymmetric absorption profile can therefore be explained by a clumpy, rotating H i gas disc seen partially in front of the central continuum source, or by ram pressure pushing the neutral gas towards the centre of the continuum source, triggering the AGN activity.